Assessing the Necessity of Routine Crossmatching for Blood Transfusion in Renal Transplantation. (December 2020) - Cheung, Douglas; Reynolds, Luke; Peng, Melin; Lee, Jason; Stewart, Robert; Pace, Kenneth; Honey, R. John D'Arcy; Ordon, Michael
Introduction: Routine crossmatch of packed red blood cells (pRBCs) is completed preoperatively at many centers despite conflicting evidence on the incidence of blood transfusions with renal transplantation. In the current economic climate, resource adjudication should be judicious and medically appropriate. The objective of this study was to determine the incidence, timing, and predictors of early postoperative pRBC transfusion in patients undergoing renal transplantation. Methods: A retrospective review of all patients undergoing renal transplantation at our institution from January 2013 to May 2016 was performed. Demographic, biochemical, and clinical parameters were recorded. The primary outcome was early postoperative transfusion, defined as an intraoperative transfusion or within 2 days of surgery. Multivariable logistic regression was performed to identify associations with early postoperative transfusion. Results: We identified 428 patients during the study period (average age 55 years, 60% male, 30% obese, 67% deceased donor, and 43% preoperative antithrombotic use). Forty (9.3%) patients required early postoperative transfusion (mean: 2.8 pRBCs/transfusion) and most did not require blood urgently. Only 20 (4.7%) patients required a transfusion intraoperatively or on the same day of surgery. Lower preoperative hemoglobin (per g/L unit: odds ratio [OR]: 0.943), female gender (OR: 2.752), and preoperative antithrombotic use (OR 2.369) were associated with a need for early postoperative transfusion. Conclusion: Transfusion in the early postoperative period following renal transplantation was less than 10%, suggesting that routine crossmatch may not be necessary for all patients. Preoperative hemoglobin, female gender, and preoperative antithrombotic use were associated with increased risk and may be useful to risk-stratify patients who require crossmatch.